TEACHER DEVELOPMENT - EXPLORATORY ACTION RESEARCH: EVIDENCE FROM ENGLISH LANGUAGE TEACHING IN UZBEKISTAN - Gulnora Nasirova, (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
training or prescribed methodologies. Increasingly, teachers are expected to reflect on their own practice and adapt to the realities of their classrooms. One approach that supports this process is Exploratory Action Research (EAR), which allows teachers to investigate their teaching while continuing their everyday work. This article explores the role of EAR in supporting professional development, with a particular focus on the Uzbek educational context. It also presents a small-scale classroom inquiry into student participation in speaking tasks. The findings suggest that EAR can help teachers better understand their learners, make more informed decisions, and gradually improve classroom interaction. At the same time, certain practical challenges remain, including time limitations and a lack of institutional support.